The Influence of Leadership, Motivation, and Organizational Culture on Employee Performance Through Job Satisfaction at PT Pegadaian Area Office Bantaeng - Akir, Akir; Nasir Hamzah, Muhammad; Sujatmiko (LP2M IBK Nitro, 2025)
The purpose of this study is to understand and analyze the influence of Leadership, Motivation, and Culture on Employee Performance through Job Satisfaction at PT Pegadaian Bantaeng Area Office, both directly and indirectly. The analysis method used is Path Analysis with SPSS and SmartPLS software, aiming to describe the actual condition of the research object to understand the influence of Leadership, Motivation, and Culture on Employee Performance through Job Satisfaction at PT Pegadaian Bantaeng Area Office by distributing questionnaires to all permanent employees in the Bantaeng Area. The research results obtained are (1) Leadership has a positive and significant influence on Job Satisfaction at PT Pegadaian Bantaeng Area Office, (2) Motivation has a positive and significant influence on Job Satisfaction at PT Pegadaian Bantaeng Area Office, (3) Culture has a positive but not significant influence on Job Satisfaction at PT Pegadaian Bantaeng Area Office, (4) Job Satisfaction has a positive and significant influence on Employee Performance at PT Pegadaian Bantaeng Area Office, (5) Leadership has a positive and significant influence on Employee Performance at PT Pegadaian Bantaeng Area Office, (6) Motivation has a negative but not significant influence on Employee Performance at PT Pegadaian Bantaeng Area Office, (7) Culture has a positive and significant influence on Employee Performance at PT Pegadaian Bantaeng Area Office, (8) Leadership has a positive and significant influence on Employee Performance through Job Satisfaction at PT Pegadaian Bantaeng Area Office, (9) Motivation has a positive and significant influence on Employee Performance through Job Satisfaction at PT Pegadaian Bantaeng Area Office and (10) Culture has a positive but not significant influence on Employee Performance through Job Satisfaction at PT Pegadaian Bantaeng Area Office.